Seroprevalence of West Nile Virus in vultures in the Centre region of Portugal - Loureiro, Filipa (2023)
West Nile Virus (WNV) is a vector-borne pathogen with zoonotic potential widely spread throughout the world. The transmission cycle is maintained by mosquitoes (mainly Culex spp.) and wild birds. Human, equines and other mammals are incidental hosts, whichare unable to amplify the agent in their blood circulation. Two lineages has been identified as disease-causing in humans and other animals: WNV-1 and WNV-2, being the latter more common in Europe.